Metal microchip and method for preparing metal microchip by vertical high-energy ball milling with temperature

CN122955948APending Publication Date: 2026-10-23NANCHANG HANGKONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611210930.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]本申请是为了克服现有技术中对于钨、钼、钒、铬等塑性较差金属,难以通过高能球磨有效制备出具有较大径厚比的金属微片的技术缺陷,因此提供了一种金属微片及带温立式高能球磨制备金属微片的方法以克服上述不足之处

Benefits of technology

其一,突破了钨、钼、钒、铬等塑性较差金属难以通过球磨方式制备微片的技术瓶颈,通过将球磨罐加热至300~400℃并结合立式高能球磨,显著提升了该类金属粉末在球磨过程中的塑性变形能力,使其从传统的脆性破碎行为转变为可控的塑性压扁行为,从而实现了微片结构的有效制备,填补了该领域的技术空白。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122955948A_ABST
    Figure CN122955948A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of metal powder metallurgy, and particularly relates to a metal flake and a method for preparing the metal flake by a vertical high-energy ball milling with temperature. The method comprises the following steps: packaging polygonal or spherical metal powder of at least one of tungsten, molybdenum, vanadium and chromium, stearic acid grinding medium and grinding balls into a ball milling tank and vacuumizing; heating the ball milling tank to 300-400 DEG C and keeping warm, and the upper limit of the temperature is lower than the boiling point of stearic acid; immediately loading the ball milling tank into a vertical high-energy ball mill after keeping warm, and performing ball milling in a vacuum environment; and obtaining the metal flake after ball milling. Through the synergistic effect of the preheating with temperature and the vertical high-energy ball milling, the flaking capacity of the metal with poor plasticity is significantly improved, the thickness of the obtained metal flake is 10-2000 nm, the diameter-thickness ratio is 10-500, and the metal flake is suitable for the fields of high-performance structural materials, electromagnetic wave absorption and electromagnetic shielding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal powder metallurgy technology, specifically to a metal micro-flake and a method for preparing metal micro-flakes using a heated vertical high-energy ball mill. Background Technology

[0002] Metal flakes, due to their unique two-dimensional geometry and excellent in-plane anisotropy, have shown significant application value in high-performance structural materials, as well as in electromagnetic wave absorption, electromagnetic shielding, and conductive and thermally conductive fillers. For example, flake carbonyl iron powder and flake silver powder have been widely used to prepare high-performance microwave absorbing coatings and conductive adhesives. However, many metallic materials with good electromagnetic or mechanical properties, such as tungsten (W), molybdenum (Mo), vanadium (V), and chromium (Cr), often fail to be effectively flattened into flakes during traditional mechanical ball milling due to their poor plasticity. Instead, they tend to undergo brittle fracture, ultimately resulting in fine granular powder. This has long limited the preparation of these materials into high-performance flakes, restricting their further application in related fields.

[0003] High-energy ball milling is a common technique for preparing metal flakes. Its basic principle is to utilize the high-speed collision, compression, and shearing action between the grinding balls and the powder to repeatedly deform the metal particles with a certain degree of plasticity, ultimately forming a thin flake structure. In this process, the ball milling temperature is a crucial process parameter. For a long time, the mainstream view in this field has been that the ball milling temperature should be controlled within a low range (e.g., 20~80℃) to avoid severe cold welding and adhesion of the metal powder due to overheating, leading to a decrease in ball milling efficiency or even preventing normal operation. Based on this understanding, a large amount of research has focused on controlling parameters such as ball milling time, ball-to-powder ratio, and rotation speed under low-temperature ball milling conditions to achieve the preparation of different metal flakes. This method has achieved relatively ideal results for metals with good plasticity such as aluminum, copper, and nickel. However, for metals with poor room-temperature plasticity such as tungsten, molybdenum, vanadium, and chromium, even with extended ball milling time, it is difficult to obtain flakes with a large aspect ratio; the product is often still mainly composed of broken fine powder.

[0004] In recent years, some researchers have begun to attempt to increase the ball milling temperature in order to improve the plastic deformation capacity of metals through thermal activation effects. For example, some literature reports the ball milling of titanium powder at 400℃ in a horizontal ball mill, but the resulting products are mainly granular rather than flake-like, indicating that simply increasing the temperature is insufficient to guarantee the formation of a flake-like structure. Another study conducted heated wet ball milling experiments on carbonyl iron powder, finding that flake-like powder with a large aspect ratio and suitable microstructure could be obtained at around 250℃. However, when the temperature exceeded 250℃, the grains grew rapidly, the internal strain decreased significantly, and the electromagnetic properties deteriorated. These works reveal the complex influence of temperature on the ball milling process, but the research subjects are all metals with good plasticity, and they do not address the potential differences in the flake formation effect caused by the type of equipment (vertical vs. horizontal). Furthermore, in the selection of grinding aids, existing studies mostly use liquid media such as silicone oil and alcohol; the stability and lubrication mechanism of these media at high temperatures require further investigation.

[0005] Overall, while existing technologies have made some progress in the sheet-forming process of specific metal systems, the following shortcomings remain: First, for metals with poor plasticity such as tungsten, molybdenum, vanadium, and chromium, an effective ball milling process route for sheet-forming has not yet been established; second, the control of ball milling temperature is mostly limited to empirical exploration, lacking a systematic understanding of the relationship between temperature window and metal plasticity and the thermal stability of grinding aids; third, the influence of equipment configuration (vertical vs. horizontal) on the morphology of high-temperature ball milling products has not received sufficient attention, and related comparative studies are rarely reported. These problems mean that the low-cost, high-efficiency preparation of metal micro-sheets with poor plasticity remains a challenging issue, urgently requiring new process ideas for breakthroughs. Summary of the Invention

[0006] This application aims to overcome the technical shortcomings of existing technologies that make it difficult to effectively prepare metal micro-sheets with a large aspect ratio using high-energy ball milling for metals with poor plasticity such as tungsten, molybdenum, vanadium, and chromium. Therefore, it provides a method for preparing metal micro-sheets using a heated vertical high-energy ball mill to overcome the above-mentioned deficiencies.

[0007] To achieve the above-mentioned objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides a method for preparing metal micro-flakes using a heated vertical high-energy ball mill, comprising the following steps: (1) The metal powder, stearic acid grinding aid, and grinding balls are packaged into a ball mill jar and vacuumed; (2) Heat the ball mill jar to 300~400℃ and keep it at that temperature, wherein the upper limit of 300~400℃ is lower than the boiling point of stearic acid; (3) After the heat preservation is completed, the ball mill jar is immediately loaded into the vertical high-energy ball mill for ball milling. The ball milling process is carried out in a vacuum environment. (4) Metal flakes were obtained after ball milling; The metal powder is at least one of tungsten, molybdenum, vanadium, and chromium, and its initial morphology is polygonal or spherical.

[0008] In the field of metal flake preparation, metals with poor plasticity, such as tungsten, molybdenum, vanadium, and chromium, tend to undergo brittle fracture rather than plastic flattening under conventional ball milling conditions due to their inherent limitations in dislocation movement and plastic deformation capabilities. This makes it difficult to obtain flake structures with a large aspect ratio, a problem that has long remained unresolved. To address this, those skilled in the art typically maintain ball milling temperatures at lower levels, believing that high temperatures will cause severe cold welding adhesion and lead to the failure of grinding aids. Meanwhile, some explorations of high-temperature ball milling have primarily focused on metal systems with better plasticity, and the resulting products are mostly granular rather than flake-like. Therefore, existing technologies lack a clear process route applicable to the preparation of metal flakes with poor plasticity, and those skilled in the art lack technical inspiration for processing metals such as tungsten, molybdenum, vanadium, and chromium into flakes through ball milling.

[0009] This application addresses the aforementioned technical challenges. Its core concept lies in recognizing that "heating" and "vertical" are not independent process parameters, but rather an organic whole requiring deep synergy to be effective. This synergistic effect further forms an inseparable technical chain with the thermal stability of the stearic acid grinding aid and the "immediate loading after heat preservation" operation sequence. Specifically, heating the ball mill to 300-400°C and holding it at that temperature aims to significantly enhance the dislocation mobility of metals such as tungsten, molybdenum, vanadium, and chromium through thermal activation, thereby reducing their resistance to plastic deformation and enabling particles that would otherwise tend towards brittle fracture to acquire the plasticity required to flatten into flakes. However, simply increasing the temperature is insufficient to guarantee the formation of a flake structure. Extensive experimental research by the applicant revealed that when metal powders are processed using a horizontal ball mill under the same temperature conditions, the resulting product remains granular. This indicates that an increase in temperature must be combined with a specific mechanical action to trigger a qualitative change. This application selects a vertical high-energy ball mill as the actuator, which takes advantage of the fact that the vertical configuration can exert a stronger combined impact, shear and friction on the powder particles during high-speed operation. This mechanical environment is consistent with the state of increased metal plasticity at high temperature, which makes the particles more inclined to plastic extension rather than break when subjected to force, thereby gradually forming a thin sheet structure.

[0010] Furthermore, this application anchors the upper temperature limit to the range of 300~400℃, and explicitly states that this upper limit is lower than the boiling point of stearic acid. The reason for choosing this parameter is that stearic acid plays multiple roles in this scheme: on the one hand, it forms a lubricating film between the powder particles and the grinding balls, reducing the tendency for cold welding between particles; on the other hand, thanks to its chemical stability within this temperature range, it ensures that it continues to play a grinding aid role throughout the ball milling process without rapidly decomposing and failing. If the temperature exceeds the boiling point of stearic acid, the grinding aid medium will deteriorate rapidly, thereby destroying the stability of the entire process system; if the temperature is too low, the dislocation movement of metals such as tungsten, molybdenum, vanadium, and chromium cannot be fully activated, and the particles still tend to break. Therefore, the temperature window of 300~400℃ is the optimal range for matching the stearic acid grinding aid medium, and the two constitute a mutually dependent and synergistic relationship.

[0011] Furthermore, due to heat loss during the transfer of the milling jar to the ball mill, if it is not installed in time, the powder temperature inside the jar will drop back to near room temperature, causing the plastic state activated by the preheating to be lost. This degenerates the ball milling process into conventional low-temperature ball milling, making micro-flake preparation impossible. This application, through the "immediate installation" operation, ensures that the powder is still in a highly plastic state of 300-400°C at the start of vertical ball milling. This ensures that the temperature activation effect and the mechanical action of vertical high-energy ball milling precisely coincide on the time axis, which is the key guarantee for the realization of the aforementioned synergistic mechanism.

[0012] As can be seen from the above scheme, this application constructs a complete process for preparing metal micro-flakes with poor plasticity by organically combining four elements: "heated preheating—stearic acid-assisted grinding—vertical high-energy ball milling—immediate installation." Among these, heated preheating solves the fundamental obstacle of insufficient metal plasticity; the vertical configuration provides a mechanical action mode that matches the high-temperature plastic state; stearic acid achieves a balance between grinding assistance and heat resistance stability within the 300-400℃ range; and immediate installation ensures the spatiotemporal consistency of temperature effects and mechanical action. These four elements are indispensable; the absence or substitution of any element will lead to a deviation from the technical solution and prevent the acquisition of the expected micro-flake product.

[0013] Experiments show that the method described in this application can significantly reduce the breakage tendency of metals such as tungsten, molybdenum, vanadium, and chromium during ball milling, and greatly improve their ability to form sheet-like shapes. The obtained metal micro-flakes have a much larger aspect ratio than conventional ball-milled products, and the sheet thickness is uniform with good surface integrity. This method lays a solid technical foundation for improving the processing performance of metals with poor plasticity such as tungsten, molybdenum, vanadium, and chromium, and promoting their application in high-performance structural materials, as well as in electromagnetic wave absorption and electromagnetic shielding.

[0014] Preferably, in step (1), the amount of stearic acid added is 0.2~3.0 wt.% of the mass of the metal powder.

[0015] Preferably, in step (1), the grinding ball is a zirconia grinding ball.

[0016] Preferably, in step (1), the vacuum is evacuated to below 10 Pa.

[0017] Preferably, in step (3), the ball milling process is carried out under a vacuum environment.

[0018] Preferably, in step (2), the heating is carried out in a vacuum drying oven, with a heating rate of 10~200℃ / min and a holding time of 20~600min.

[0019] Preferably, the interval between the end of step (2) heat preservation and the end of step (3) installation should not exceed 5 minutes.

[0020] Preferably, in step (3), the ball-to-material mass ratio of the vertical high-energy ball mill is 10~40:1, the ball milling speed is 300~700 r / min, and the ball milling time is 0.5~8 h.

[0021] Preferably, the average particle size D50 of the metal powder is 10~100 μm.

[0022] Secondly, the present invention also provides a metal microsheet, which is prepared by the method described above, wherein the thickness of the metal microsheet is 10~2000 nm and the aspect ratio is 10~500; the material of the metal microsheet is tungsten, molybdenum, vanadium or chromium.

[0023] Therefore, the method for preparing metal micro-flakes using heated vertical high-energy ball milling provided in this application has the following advantages compared to the prior art: Firstly, it breaks through the technical bottleneck of preparing micro-flakes from metals with poor plasticity such as tungsten, molybdenum, vanadium, and chromium by ball milling. By heating the ball mill jar to 300-400℃ and combining it with vertical high-energy ball milling, the plastic deformation ability of such metal powders during the ball milling process is significantly improved, transforming it from the traditional brittle crushing behavior to controllable plastic flattening behavior, thereby realizing the effective preparation of micro-flake structures and filling the technical gap in this field.

[0024] Secondly, the prepared metal microplates have a large aspect ratio and good sheet uniformity. The thickness can be controlled at the nanometer to submicrometer level, and the aspect ratio can reach hundreds of times. Moreover, the sheet surface is smooth and the edges are regular, avoiding the fragmentation and irregular morphology problems commonly encountered in conventional ball milling, thus providing an ideal geometric structure basis for subsequent functional applications.

[0025] Thirdly, by selecting stearic acid grinding aid media and matching it with a temperature window of 300~400℃, the chemical stability of the grinding aid media is maintained throughout the ball milling process while effectively suppressing powder cold welding and adhesion at high temperatures. This avoids process runaway caused by the decomposition and failure of the grinding aid, thereby improving the repeatability and stability of the process.

[0026] Fourth, the adoption of the vertical high-energy ball mill and the coordination of the "installation immediately after heat preservation" operation sequence fully leverage the synergistic effect of the high-temperature plastic state and the combined mechanical action of the vertical configuration. This allows the thermal activation effect and mechanical deformation effect to be precisely coupled in time and space, significantly reducing energy loss and process complexity, shortening the ball milling cycle, and improving production efficiency.

[0027] Fifth, the entire process is carried out under vacuum, which effectively avoids the oxidation of metal powder at high temperatures and ensures the purity and performance stability of the product. At the same time, the method has a simple process flow, strong equipment versatility, and does not require additional complex post-processing procedures, and has good prospects for industrial application. Attached Figure Description

[0028] Figure 1 This is an electron microscope image of the vanadium microsheets prepared in Example 1.

[0029] Figure 2 This is an electron microscope image of the vanadium powder prepared in Comparative Example 1.

[0030] Figure 3 This is an electron microscope image of the tungsten microsheets prepared in Example 2.

[0031] Figure 4 This is an electron microscope image of the tungsten powder prepared in Comparative Example 2.

[0032] Figure 5 This is an electron microscope image of the molybdenum microplates prepared in Example 3.

[0033] Figure 6 This is an electron microscope image of the molybdenum powder prepared in Comparative Example 3.

[0034] Figure 7 Electron micrograph of the titanium powder prepared in Comparative Example 4; Among them, (a) is a ball-to-material ratio of 1:1, (b) is a ball-to-material ratio of 2:1, (c) is a ball-to-material ratio of 3:1, (d) is a ball-to-material ratio of 4:1, and (e) is a ball-to-material ratio of 5:1.

[0035] Figure 8 This is an electron microscope image of a vertically ball-milled titanium microsheet, as shown in Comparative Example 5.

[0036] Figure 9 This is an electron microscope image of the horizontally ball-milled titanium powder in Comparative Example 5. Detailed Implementation

[0037] The present invention will be further described below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.

[0038] Example 1 Using 1.0 wt.% stearic acid as the grinding aid, a mixture of stearic acid, grinding balls, and high-purity vanadium metal powder was packaged into a ball mill jar and evacuated to 10 Pa. The jar was then placed in a vacuum drying oven and heated to 300°C at a rate of 50°C / min, and held at that temperature for 30 min. Immediately after the holding period, the mixture was loaded into a vertical ball mill for grinding. Zirconia grinding balls were used, with a ball-to-powder mass ratio of 20:1. The milling speed was 450 r / min, and the milling time was 2 hours, yielding vanadium metal flakes, such as... Figure 1 As shown.

[0039] Comparative Example 1 The conditions for Comparative Example 1 were basically the same as those for Example 1, except that Comparative Example 1 did not undergo preheating, and ball milling was performed using the same amount of grinding aid media and the same ball milling process. The resulting vanadium metal powder was refined, such as... Figure 2 As shown.

[0040] Example 2 Using 1.0 wt.% stearic acid as the grinding aid, a mixture of stearic acid, grinding balls, and high-purity tungsten metal powder was packaged into a ball mill jar and evacuated to 10 Pa. The jar was then placed in a vacuum drying oven and heated to 350°C at a rate of 50°C / min, and held at that temperature for 30 min. Immediately after the holding period, the powder was loaded into a vertical ball mill for grinding. Zirconia grinding balls were used, with a ball-to-powder mass ratio of 20:1. The milling speed was 500 r / min, and the milling time was 2 hours, yielding tungsten metal flakes, such as... Figure 3 As shown.

[0041] Comparative Example 2 The conditions for Comparative Example 2 were basically the same as those for Example 2, except that Comparative Example 2 did not undergo preheating, and ball milling was performed using the same amount of grinding aid media and the same ball milling process. The resulting tungsten metal powder was refined, such as... Figure 4 As shown.

[0042] Example 3 Using 1.0 wt.% stearic acid as the grinding aid, a mixture of stearic acid, grinding balls, and high-purity molybdenum metal powder was packaged into a ball mill jar and evacuated to 10 Pa. The jar was then placed in a vacuum drying oven and heated to 350°C at a rate of 50°C / min, and held at that temperature for 30 min. Immediately after the holding period, the mixture was loaded into a vertical ball mill for ball milling. Zirconia grinding balls were used, with a ball-to-powder mass ratio of 20:1. The ball milling speed was 500 r / min, and the milling time was 2 hours, yielding molybdenum metal flakes, such as... Figure 5 As shown.

[0043] Comparative Example 3 The conditions for Comparative Example 3 and Example 3 were basically the same, except that: the comparative example did not undergo preheating, and ball milling was performed using the same amount of grinding aid media and the same ball milling process, resulting in finer molybdenum metal powder, such as... Figure 6 As shown.

[0044] Example 4 Using 0.2 wt.% stearic acid as the grinding aid, stearic acid, grinding balls, and high-purity vanadium metal powder were packaged into a ball mill jar and evacuated to 10 Pa. The jar was then placed in a vacuum drying oven and heated to 200°C at a rate of 10°C / min, and held at that temperature for 600 min. Immediately after the holding period, the powder was loaded into a vertical ball mill for grinding. Zirconia grinding balls were used, with a ball-to-powder mass ratio of 40:1. The milling speed was 750 r / min, and the milling time was 0.5 hours, yielding vanadium metal flakes.

[0045] Example 5 Using 3.0 wt.% stearic acid as the grinding aid, a mixture of stearic acid, grinding balls, and high-purity vanadium metal powder was packaged into a ball mill jar and evacuated to 10 Pa. The jar was then placed in a vacuum drying oven and heated to 400°C at a rate of 200°C / min, and held at that temperature for 20 min. Immediately after the holding period, the mixture was loaded into a vertical ball mill for grinding. Zirconia grinding balls were used, with a ball-to-powder mass ratio of 10:1. The milling speed was 300 r / min, and the milling time was 8 hours, yielding vanadium metal flakes.

[0046] Example 6 Using 3.0 wt.% stearic acid as the grinding aid, stearic acid, grinding balls, and high-purity chromium metal powder were packaged into a ball mill jar and evacuated to 10 Pa. The jar was then placed in a vacuum drying oven and heated to 400°C at a rate of 100°C / min, and held at that temperature for 60 min. Immediately after the holding period, the powder was loaded into a vertical ball mill for grinding. Zirconia grinding balls were used, with a ball-to-powder mass ratio of 10:1. The milling speed was 500 r / min, and the milling time was 6 hours, yielding chromium metal flakes.

[0047] Comparative Example 4 This comparative example is compared with the existing literature "D. Chen, B. Liu, G. Sun, et al., High-temperature ball milling: An efficient method to fabricate Ti and its alloypowder for additive manufacturing, Advanced Powder Technology 35 (2024)104377".

[0048] This paper describes a horizontal ball milling process used at 400℃ to ball mill Ti powder with an average particle size (D50) of 38.9 μm. The morphology of the prepared powder is as follows: Figure 7 As shown in the figure, the Ti powder in the literature did not form metal flakes after ball milling and remained in granular form.

[0049] Comparative Example 5 This comparative example was conducted to compare the effects of horizontal and vertical ball mills, hence the comparative experiment.

[0050] Using 1.0 wt.% stearic acid as the grinding aid, a mixture of stearic acid, grinding balls, and high-purity Ti metal powder (average particle size D50 of 40 μm) was packaged into a ball mill jar and evacuated to 10 Pa. The jar was then placed in a vacuum drying oven and heated to 350°C at a rate of 50°C / min, and held at that temperature for 30 min. Immediately after the holding period, the powder was loaded into a ball mill and subjected to the same grinding process using both vertical and horizontal ball mills. Zirconia grinding balls were used at a ball-to-powder mass ratio of 20:1, the milling speed was 500 r / min, and the milling time was 2 hours to obtain Ti metal powder. Figure 8 As shown, this is the morphology of Ti powder produced by vertical ball milling, which is a typical metal flake. Figure 9 The morphology of Ti powder produced by horizontal ball milling is shown, which is significantly refined into granules.

Claims

1. A method for preparing metal micro-flakes using a heated vertical high-energy ball mill, characterized in that, Includes the following steps: (1) The metal powder, stearic acid grinding aid, and grinding balls are packaged into a ball mill jar and vacuumed; (2) Heat the ball mill jar to 300~400℃ and keep it at that temperature, wherein the upper limit of 300~400℃ is lower than the boiling point of stearic acid; (3) After the heat preservation is completed, the ball mill jar is immediately loaded into the vertical high-energy ball mill for ball milling. The ball milling process is carried out in a vacuum environment. (4) Metal flakes were obtained after ball milling; The metal powder is at least one of tungsten, molybdenum, vanadium, and chromium, and its initial morphology is polygonal or spherical.

2. The method for preparing metal micro-flakes using a heated vertical high-energy ball mill according to claim 1, characterized in that, In step (1), the amount of stearic acid added is 0.2~3.0 wt.% of the mass of the metal powder.

3. The method for preparing metal micro-flakes using a heated vertical high-energy ball mill according to claim 1, characterized in that, In step (1), the grinding ball is a zirconia grinding ball.

4. The method for preparing metal micro-flakes using a heated vertical high-energy ball mill according to claim 1, characterized in that, In step (1), the vacuum is evacuated to below 10 Pa; In step (3), the ball milling process is carried out under a vacuum environment.

5. The method for preparing metal micro-flakes using a heated vertical high-energy ball mill according to claim 1, characterized in that, In step (2), the heating is carried out in a vacuum drying oven at a heating rate of 10~200℃ / min and a holding time of 20~600min.

6. The method for preparing metal micro-flakes using a heated vertical high-energy ball mill according to claim 1, characterized in that, The interval between step (2) after the insulation is completed and step (3) after the installation is completed shall not exceed 5 minutes.

7. The method for preparing metal micro-flakes using a heated vertical high-energy ball mill according to claim 1, characterized in that, In step (3), the ball-to-material mass ratio of the vertical high-energy ball mill is 10~40:1, the ball milling speed is 300~700 r / min, and the ball milling time is 0.5~8 h.

8. The method for preparing metal micro-flakes using a heated vertical high-energy ball mill according to claim 1, characterized in that, The average particle size D50 of the metal powder is 10~100 μm.

9. A metal microsheet, prepared by the method according to any one of claims 1 to 8, The thickness of the metal microplate is 10~2000 nm, and the aspect ratio is 10~500; The metal micro-flakes are made of tungsten, molybdenum, vanadium, or chromium.

10. The application of the metal microsheets as described in claim 9 in the fields of high-performance structural materials and electromagnetic wave absorption and electromagnetic shielding functional materials.